2018
DOI: 10.1017/cem.2018.435
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific, high-sensitivity cardiac troponin T cut-off concentrations for ruling out acute myocardial infarction with a single measurement

Abstract: ObjectiveSex-specific diagnostic cut-offs may improve the test characteristics of high-sensitivity troponin assays for the diagnosis of myocardial infarction (MI). The objective of this study was to quantify test characteristics of sex-specific cut-offs of a single, high-sensitivity cardiac troponin T (hs-cTnT) assay for 7-day MI in patients with chest pain.MethodsThis observational cohort study included consecutive emergency department (ED) patients with suspected cardiac chest pain from four Canadian EDs who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Presumably due to gender-specific differences in diagnoses and treatment and due to a higher rate of acute interventional need for therapy, more men were transferred to the catheterization laboratory or to the intensive care unit. The trend in male patients to be discharged directly from the CPU remains unclear but may be due to stricter rule-out parameters in men [35, 36]. The low in-CPU mortality without gender differences may be caused by good guideline adherence in certified German CPUs.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably due to gender-specific differences in diagnoses and treatment and due to a higher rate of acute interventional need for therapy, more men were transferred to the catheterization laboratory or to the intensive care unit. The trend in male patients to be discharged directly from the CPU remains unclear but may be due to stricter rule-out parameters in men [35, 36]. The low in-CPU mortality without gender differences may be caused by good guideline adherence in certified German CPUs.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study confirmed no advantage in risk prediction when using sex-specific reference values, the risk in women was increased at levels of 10-12 ng/L, which is below the set standard point of 14 ng/L [93]. A recent observational study, focused on the diagnostic performance of several sex-specific hs-cTnT cut-offs for the rule-out of MI, showed an improved specificity with the adoption of different threshold levels [94]. These findings were also consistent with a recent Chinese study in which sex-specific cut-offs were calculated in an original reference population and then further stratified according to age.…”
Section: Application Of Sex-specific Cut-offs In Clinical Practicementioning
confidence: 99%
“…3,6,7 While studies have previously focused on improving ruling-in MI with sexspecific cut-offs, in this issue, McRae and colleagues explore the concept of ruling-out MI with a single Roche Elecsys® high-sensitivity cardiac troponin T (hs-cTnT), using several cut-off levels relative to the limit of detection (< 5 ng/L) and the Food and Drug Administration-approved limit of quantification (< 6 ng/L). 8 The 99th percentile reference limit for this assay is 14 ng/L. The study found that sex-specific cut-offs may improve the classification performance and could lead to rule out MI among more patients on ED arrival.…”
Section: Introductionmentioning
confidence: 83%